Which competences for whom? Supporting the supporters of work-related L2 development by migrants and ethnic minorities - Matilde Grünhage-Monetti (Peoples' Friendship University of Russia (RUDN University), 2020)
Competences is one of the key words used to describe performance improvement in language learning and teaching and management training. Training is not just concerned with knowledge but with competence - the ability to perform successfully. Competences and the achievement of competency are key indicators used in quality assurance and assessment of student success and course validity. This paper takes a systemic stance on how to support migrant and ethnic minority learners develop their work-related communicative skills in the language of the country of residence (L2). It looks beyond the classroom at other places where work-related L2 learning take place and/or can be supported, including job centres and the workplace itself. It considers other actors than L2 teachers and providers including employers, managers and labour administration staff. Based on small-scale empirical research into work-related L2 teaching and learning practice, the article presents some findings of the Language for Work Network (LfW) and describes competences, which have been found helpful in practice to different actors supporting L2 development for and at work.